2018
DOI: 10.1002/jeab.456
|View full text |Cite
|
Sign up to set email alerts
|

A nonsequential approach to the study of operant renewal: a reverse translation

Abstract: ABA renewal is a model of treatment relapse that describes the recurrence of severe problem behavior when behavior learned in one context (e.g., home; A) and treated in a separate context (e.g., clinic; B) reemerges when the original context is reintroduced (A). However, in the typical environment and during the usual course of treatment for severe problem behavior, the target behavior is exposed to the baseline context periodically (e.g., the child returns home after several hours in a clinic setting). Due to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
22
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 21 publications
(31 reference statements)
1
22
0
Order By: Relevance
“…First, as described previously, Sullivan et al' () paper reported negligible differences in renewal between their Sequential and Nonsequential assessments. Effectively, their data suggested that refining laboratory renewal preparations to capture the potential influences of context/contingency changes present in outpatient treatment for severe destructive behavior may have little implication for translational research on renewal (as no such influences appeared to be present in their study).…”
Section: Discussionmentioning
confidence: 66%
See 4 more Smart Citations
“…First, as described previously, Sullivan et al' () paper reported negligible differences in renewal between their Sequential and Nonsequential assessments. Effectively, their data suggested that refining laboratory renewal preparations to capture the potential influences of context/contingency changes present in outpatient treatment for severe destructive behavior may have little implication for translational research on renewal (as no such influences appeared to be present in their study).…”
Section: Discussionmentioning
confidence: 66%
“…The present experiment systematically replicated Sullivan and colleagues' () procedure while addressing the concerns raised above as follows. First, rat subjects were used to control for potential mediation of behavior during the renewal test by verbal processes.…”
mentioning
confidence: 64%
See 3 more Smart Citations